Projective synchronization via feedback controller of fractional-order chaotic systems. (2nd September 2020) - Khan, Ayub; Bhat, Muzaffar Ahmad
ABSTRACT: This paper presents a type of fractional-order chaotic systems with fractional order greater than one, on which the projective synchronization via feedback controller has been applied. Through literal presumptions, the projective synchronization is approached. To validate the efficiency of the suggested scheme, the considered systems have been simulated. The simulations have been performed by using Matlab.